Affordable air-ground mobile mapping system for precise forestry applications - J. Bedkowski; M. Kulicki; M. Kulicki; K. Stereńczak; M. Matecki (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Precise forest inventory in difficult terrain remains challenging due to mobility constraints and canopy occlusion. This paper presents an affordable air-ground mobile mapping system combining shoulder-mounted double LiDAR with a lightweight FPV drone-based LiDAR. We developed an extrinsic calibration method for dual orthogonally-mounted sensors and implemented a comprehensive processing pipeline incorporating LiDAR odometry, pose graph SLAM, and multi-view Normal Distributions Transform. Field experiments demonstrate successful air-ground data fusion for tree stem detection and dendrometric parameter extraction. The system was validated in extreme environments including a cave survey, proving versatility in difficult terrain. All software components are released as open-source tools: https://github.com/MapsHD/HDMapping.